2020
DOI: 10.1177/0733464819898315
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of Older Persons in Jamaica: Characteristics, Burden, and Associated Factors

Abstract: Objective: The objective of this study was to determine and characterize caregiver burden among caregivers of community-dwelling older persons in Jamaica. Method: A nationally representative cross-sectional study was done among persons providing noninstitutional care for a single person (≥60 years). The Zarit Burden Interview (ZBI) and a structured questionnaire were administered to 180 caregivers from four geographic health regions. Results: The ZBI scores ranged from 0 to 56 (median = 15). Independently asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Caregiver burden has been defined as the type of stress or strain that caregivers experience resulting from the problems and challenges they face in their interactions with the care recipients (Zarit et al, 1980). A number of studies investigating the process of caring for an older relative have found that family caregivers consistently report high levels of burden (Bainbridge et al, 2009;James et al, 2020;Khalaila & Litwin, 2011;Kim et al, 2012;Lynch et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Caregiver burden has been defined as the type of stress or strain that caregivers experience resulting from the problems and challenges they face in their interactions with the care recipients (Zarit et al, 1980). A number of studies investigating the process of caring for an older relative have found that family caregivers consistently report high levels of burden (Bainbridge et al, 2009;James et al, 2020;Khalaila & Litwin, 2011;Kim et al, 2012;Lynch et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One hundred and eighty caregivers across four geographic health regions completed the ZBI. Details of sampling procedure and sample size selection have been previously published (Holder-Nevins et al, 2018;James et al, 2020).…”
Section: Me Thodologymentioning
confidence: 99%
“…Another study that examined caregiver burden among 180 caregivers of community dwelling older persons in Jamaica found that children and grandchildren of care recipients were three times more likely to report caregiver burden than formally employed caregivers [20]. The study noted that caregivers aged 45 to 65 years were 5.5 times more likely to report higher caregiver burden than those 44 years and younger.…”
Section: Unpaid Carementioning
confidence: 98%
“…In Jamaica, as in many LMICs, there is no LTC insurance, LTC is gendered (mostly female), mostly informal (from family members and volunteers), and without financial or technical support from the state [5,[17][18][19][20]. Further, women from lower income, often rural communities, who migrate to work as domestics in urban households, contribute to a large group of LTC providers because the supervision and care assistance they provide are technically unpaid; they are not paid for care work per se but for household work not-specific to the target care-recipient [17].…”
Section: The Current Long-term Care System For Older Persons In Jamaicamentioning
confidence: 99%
See 1 more Smart Citation